THE IMPLEMENTATION OF HALAL PRODUCT GUARANTEES FOR TRADITIONAL FOOD ENTREPRENEURS BY THE INDONESIAN ULEMA COUNCIL ACCORDING TO ISLAMIC LAW AND LAW NUMBER 33 OF 2014 CONCERNING HALAL PRODUCT GUARANTEES IN BENGKULU CITY - Agri Theo Renaldo; Sirman Dahwal; Akhmad Muslih (Bengkoelen Justice : Jurnal Ilmu Hukum, 2023)
The writing of this research aims to (1) find out and analyze the implementation of halal product guarantees for traditional food entrepreneurs by the Indonesian Ulema Council in Bengkulu City, (2) find out and analyze the obstacles to the implementation of halal product guarantees for traditional food entrepreneurs by the Indonesian Ulema Council in Bengkulu City, and  (3) find out and analyze the efforts to overcome the obstacles to the implementation of halal product guarantees for traditional food entrepreneurs by the Indonesian Ulema Council in Bengkulu City. This research used a descriptive approach and the data were gathered through primary, secondary, and tertiary legal materials. The results of the research explained that the implementation of halal product guarantees for traditional food entrepreneurs by the Indonesian Ulema Council in Bengkulu City is begun with traditional food entrepreneurs carrying out online registration at the Bengkulu Provincial Regional Office of the Ministry of Religious Affairs. The obstacles to the implementation of halal product guarantees for traditional food entrepreneurs by the Indonesian Ulema Council in Bengkulu City included; a lack of legal awareness of traditional food businesses to obtain halal product guarantee certificates, and the efforts made by the Institute for the Study of Food, Drugs, and Cosmetics of the Indonesian Ulema Council of Bengkulu Province to socialize Halal Certification and the importance of halal food and increase the number of Halal Inspection Agencies to all regions in Bengkulu province, as well as increase the number of auditors of the Institute for the Study of Food, Drugs, and Cosmetics of the Indonesian Ulema Council to the regions of Bengkulu Province. Keywords: Halal product guarantee, entrepreneurs, traditional food, the Indonesian Ulema Council, Islamic law, Law Number 33 of 2014.